The Utilization of Google Classroom in Social Studies Learning - Muklis Riyanto; Yunita Yunita; Jamilah Jamilah; Shella Monica; Zuhri Zuhri; Agung Subakti; Agussalim Agussalim; Desi Tri Anggereni; Elce Purwandari (Universitas Pahlawan Tuanku Tambusai, 2022)
Google Classroom is designed as a learning medium that is used online which is simpler to use, does not use too much data, and is not complicated so it is easy to operate on smartphones with Android and iOS systems. The purpose of this study was to identify the use of google classroom in social studies learning in grade V elementary schools. The quantitative method used is a survey. The data was obtained through a survey sheet on Google Forms and then a quantitative analysis was carried out. The sample consisted of 36 students in class V of Madrasah Ibtidaiyah (MI) Miftahul Huda Kosgoro, Musi Rawas. The research results from the 10 aspects covered in the questionnaire show that Google Classroom is the right application as a learning medium because it is easy to use, does not use a lot of data, learning materials can be understood, students can be controlled so that students enjoy learning using Google Classroom, therefore Google Classroom Useful during a pandemic. This research is new because it has never been done before at MI Miftahul Huda Kosgoro. The expected contribution to research can provide knowledge for other schools that want to use Google Classroom as a learning medium, and provide a reference for other researchers who want to conduct research related to Google Classroom as a learning medium that is used in the learning process.